Le relevé habité face à la vulnérabilité résidentielle : intérêts et limites - Yankel Fijalkow (Association Internationale des Sociologues de Langue Française, 2021)
In global cities, tensions on the real estate market are leading to an increase in housing overcrowding. This article proposes a methodological reflection on the “housing survey”, which is a social science tool applied to architecture that allows spatial measurement of housing conditions. It therefore looks at the history of the method, its contribution to the analysis of inhabitants' strategies in terms of comfort. A recent survey on social housing inhabitants (and therefore safe from the crisis) illustrates the method.